O futebol explica o Brasil: o caso da Copa de 70 - Guterman, Marcos (2006)
This dissertation is aimed at understanding the relations between soccer, politics and society in Brazil, viewed by the entire world as the Country of Soccer . The intention here is to consider soccer as one of the most important vehicles used by Brazilians to express themselves and to overcome their regional and social differences. This approach is urgent, because this mainstream sport, although it mobilizes the entire country during the most part of the year, and for the last decades, have always been treated as a minor issue by the Brazilian academic elite. The climax of these relations between soccer and politics -- and, equally, the climax of the national intellectuals prejudice against soccer -- happened during the 70 World Cup, and that s why this event was chosen to be studied. Viewed by the leftist thinking as the proof that soccer can be used to manipulate people, the 70 World Cup is the materialization of a certain national ideal -- which, of course, served to the dictatorship interests, but, at same time, and maybe in first place, became the environment of an authentic expression of joy because of the country s superiority in an area so esteemed by the Brazilians. This expression could have also served to overflow feelings suppressed by the repressive system settled in the country, and the huge street parties to celebrate the Brazilian victories, in many moments, can have been also opportunities to reoccupy the public places, kidnapped by the dictatorship. This work was written basically using the account made by the newspapers of that time, in order to rebuild that environment. Although there was censorship, the newspapers have registered in true colors all that atmosphere of crisis, tension, joy and manipulation which was created during the 70 World Cup and because of the dictatorship project designed to transform Brazil into a powerful and united country